T1 High glucose and myocardial ischaemia/reperfusion injury: the role of the sodium/glucose transporter, SGLT1. (26th October 2016) - Bell, RM; Jasem, H; Harding, I; Almalki, A; Arjun, S; Yellon, DM
Abstract : Background: Hyperglycaemia, frequently found at the time of acute myocardial infarction, is associated with excess cardiovascular mortality. The sodium-glucose transporter SGLT1 is present in mammalian myocardium, but its role in acute ischaemia/reperfusion injury is currently unknown. We hypothesise high glucose at reperfusion increases infarct size following injurious ischaemia and this excess injury can be ameliorated by inhibition of SGLT1. Methods and results: Langendorff-perfused Sprague-Dawley rat (SDR) heart were subjected to 35 min regional ischaemia and 60min variable glucose (3.5–22 mmol/L) reperfusion, with osmolality controlled by reciprocal dose mannitol. Reperfusion High Glucose (RHG) significantly dose-dependently increased infarct size (45 to 65%, p < 0.05). Phlorizin (3 micromol/L), an SGLT1/2 inhibitor, abrogated the excess injury associated with RHG in Langendorff-perfused SDR heart. Surprisingly however, RHG in isolated primary SDR cardiomyocytes did not result in excess cell death; therefore SDR tissue distribution of SGLT1 was ascertained using rtPCR. Expression was found in kidney, gut, whole heart and aorta, but not skeletal muscle. Isolated cardiomyocytes did not express SGLT1: myocardial expression was limited to non-myocyte cells. Discussion and conclusion: We demonstrate for the first time that high glucose at reperfusion exacerbates myocardial injury following lethal myocardial ischaemia that can be ameliorated by inhibition of SGLT, which appears not directly targeted at cardiomyocytes, but rather non-myocyte myocardial cell populations. These data therefore provide the first data for a novel repurposing of SGLT inhibitors in non-diabetic patients presenting with acute coronary syndromes complicated by hyperglycaemia, and provides a tantalising insight into the mechanisms of hyperglycaemic-driven excess cardiovascular mortality.